Sphenoid bone dysplasia - a case of unresolved headache in primary care - Said, Abdul Hadi; Tg Arif @ Tg Zainuddin, Tg Putri Syarizan (Lincoln University College, 2022)
Headache is a very common presenting symptom in patients seeking treatment in primary care. Although most of it is primary headache, physicians may easily miss the diagnosis of secondary headache. Therefore, we need to equip ourselves with adequate knowledge together with a good and thorough physical examination to avoid missing a diagnosis of secondary headache. In addition to that, for a patient presenting with chronic headache, it is very important for us to always review our diagnosis and our management. We reported a case of sphenoid bone fibrous dysplasia who presented with severe recurrent headache despite being given treatment, analgesics and even propranolol for migraine. Fibrous dysplasia accounts for approximately 5 to 7 percent of benign bone tumours. He presented to the primary care clinic multiple times before the imaging was ordered. Subsequent MRI showed fibrous dysplasia of the right lesser wing of the sphenoid bone. After the surgery, the headache improved as well as his quality of life.